KESANTUNAN IMPERATIF GURU BAHASA INDONESIA DALAM PEMBELAJARAN DI KELAS X SMA TA’MIRIYAH SURABAYA - Azizah, Nur Fitriayatul; Burhanuddin, Ahmad; Suhartono, Suhartono; Effendri, Yunis (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Imperative Politeness of Indonesian Language Teachers in Learning in Class X SMA Ta'miriyah Surabaya. This research is qualitative descriptive research that aims to describe the important utterances of SMA Ta'miriyah teachers in Surabaya. The data for this research are the utterances of Indonesian teachers at SMA Ta'miriyah Surabaya, which contain imperative linguistic and pragmatic politeness sentences. The source of the data is the spoken utterances of Indonesian teachers in SMA during the learning process in class. The results of the study show that the imperative politeness of Indonesian language teachers in linguistic imperative politeness is characterized by expressions marking politeness, namely please, try, please, come on, and beg. Imperative pragmatic politeness that appears in this study is divided into two, categories: pragmatic politeness of declarative speech and pragmatic politeness of interrogative speech. Among the declarative utterances are the politeness of orders, prohibitions, and invitations; and interrogative speech as an expression of the pragmatic politeness of prohibitions and orders.